Smaller shrines around Banganga Tank - Ghosh, Ayan (2023)
Numerous temples, samadhis, and open shrines are scattered around Walkeshwar. There are kuldevta shrines located inside homes and protective deities are placed in wall niches and over doorways. Stone relics collected from the older Walkeshwar Temple are assembled under the shade of the sacred peepal tree.